2000
DOI: 10.1523/jneurosci.20-12-04524.2000
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Postsynaptic Density-95/Guanylate Kinase Domain-Associated Protein Complex with a Light Chain of Myosin-V and Dynein

Abstract: NMDA receptors interact directly with postsynaptic density-95 (PSD-95), a scaffold protein that organizes a cytoskeletal- signaling complex at the postsynaptic membrane. The molecular mechanism by which the PSD-95-based protein complex is trafficked to the postsynaptic site is unknown but presumably involves specific motor proteins. Here we demonstrate a direct interaction between the PSD-95-associated protein guanylate kinase domain-associated protein (GKAP) and dynein light chain (DLC), a light chain subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
217
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(231 citation statements)
references
References 57 publications
8
217
1
5
Order By: Relevance
“…It has recently been suggested that electrical activity controls the size and number of spines 21,22,[39][40][41][42] , and that the expression of glutamate receptors is tightly regulated by abundant cytoskeletal structures present in spines [3][4][5] . One can therefore surmise that spine structures are a key determinant of synaptic efficacy via control of the distribution of the AMPA receptors 9,10,43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has recently been suggested that electrical activity controls the size and number of spines 21,22,[39][40][41][42] , and that the expression of glutamate receptors is tightly regulated by abundant cytoskeletal structures present in spines [3][4][5] . One can therefore surmise that spine structures are a key determinant of synaptic efficacy via control of the distribution of the AMPA receptors 9,10,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonstationary fluctuation analysis was performed based on the following equation (4) Here, σb 2 stands for base line variance; i, single channel current; and N, the number of AMPA receptors 37 . The 2pEPSCs were filtered at 2 kHz and sampled at 10 kHz.…”
Section: Analysis Of 2pepscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The splice variant ACE however is exclusively detected in human epidermal melanocytes (unpublished results). In rat brain, the specific myosin Va variant ABCE appears together with dynein and their common LC DLC8 in a coimmunoprecipitable complex with a postsynaptic scaffold protein that organizes a cytoskeletal-signaling complex at the postsynaptic membrane (63). Creating different splice variants of a particular gene are nature's tool to regulate, e.g.…”
Section: Alternative Splicing: Making the Motor Complexes Even More Cmentioning
confidence: 99%
“…Detailed kinetic and thermodynamic characterization of this interaction using monoand dimeric myo5a fragments revealed that the dissociation constant is somewhat weaker than that of the canonical motifs(~1-5 M for a monomeric peptide) andbivalency of the ligand leads to pronounced avidity (18). hypothesized that DYNLL may provide direct physical linkage between the motor and the cargos (26,28,29). However, as the majority of the binding partners (including the motors) are dimeric, and therefore they are bivalent ligands of LC8 and the formation of highly stable dimer-to-dimer complexes is preferred (18).…”
mentioning
confidence: 99%